Revisiting the Relationship Between Blood Pressure and Insulin-Like Growth Factor-1 - Schutte, Aletta Elisabeth; Volpe, Massimo; Tocci, Giuliano; Conti, Elena (Hypertension (Dallas, Tex. 1979), 2014)
Conflicting evidence exists on the relationship between blood pressure (BP) and insulin-like growth factor-1 (IGF-1). We reviewed available articles and pooled extrapolated regression coefficients for the association between BP and total IGF-1 as reported in the literature and included additional data from 912 individuals from the general population. We identified 20 studies including 11 704 subjects. We also measured total IGF-1, insulin-like binding protein-3, and BP in 912 black and white men and women from South Africa (aged 20–70 years). When plotting positive and negative weighed regression coefficients (29 data points) against IGF-1, we found a significant positive relationship ( r =0.31; P <0.001; n=11 704) intercepting the 0 point at 191 ng/mL IGF-1, suggesting an inverse BP/IGF-1 relationship in low IGF-1 conditions, and a positive relationship in overtly high IGF-1 conditions. In conclusion, our findings suggest that the relationship between BP and IGF-1 is dependent on, or related to, IGF-1 concentrations, as an expression of direct or reverse causality. Low IGF-1 bioavailability (associated with aging and vascular deterioration), resistance to IGF-1, and the complex interplay between IGF-1 and other vasoactive hormones could mask the vasoprotective functions of IGF-1 in cross-sectional studies or could modify their functions in prospective studies.